How many physicians does Canada need to care for our aging population? - Roos, N P (1998)
BACKGROUND: There is concern that the aging of Canada's population will strain our health care system. The authors address this concern by examining changes in the physician supply between 1986 and 1994 and by assessing the availability of physicians in 1994 relative to population growth and aging, and relative to supply levels in the benchmark province of Alberta. METHODS: Physician numbers were obtained from the Canadian Institute for Health Information. The amount of services provided by each specialty to each patient age group was analysed using Manitoba physician claims data. Population growth statistics were obtained from Statistics Canada. Age- and specialty-specific utilization data and age-specific population growth patterns were used to estimate the number and type of physicians that would have been required in each province to keep up with population growth between 1986 and 1994, in comparison with actual changes in the physician numbers. Physician supply in Alberta was used as a benchmark against which other provinces were measured. RESULTS: Overall, Canada's physician supply between 1986 and 1994 kept pace with population growth and aging. Some specialties grew much faster than population changes warranted, whereas others grew more slowly. By province, the supply of general practitioners (GPs) grew much faster than the population served in New Brunswick (16.6%), Alberta (6.5%) and Quebec (5.3%); the GP supply lagged behind in Prince Edward Island (-5.4%). Specialist supply outpaced population growth substantially in Nova Scotia (10.4%), Newfoundland (8.5%), New Brunswick (7.3%) and Saskatchewan (6.8%); it lagged behind in British Columbia (-9.2%). Using Alberta as the benchmark resulted in a different assessment: Newfoundland (15.5%) and BC (11.7%) had large surpluses of GPs by 1994, whereas PEI (-21.1%), New Brunswick (-14.8%) and Manitoba (-11.1%) had substantial deficits; Quebec (37.3%), Ontario (24.0%), Nova Scotia (11.6%), Manitoba (8.2%) and BC (7.6%) had large surpluses of specialists by 1994, whereas PEI (-28.6%), New Brunswick (-25.9%) and Newfoundland (-23.8%) had large deficits. INTERPRETATION: The aging of Canada's population poses no threat of shortage to the Canadian physician supply in general, nor to most specialist groups. The marked deviations in provincial physician supply from that of the benchmark province challenge us to understand the costs and benefits of variations in physician resources across Canada and to achieve a more equitable needs-based availability of physicians within provinces and across the country.